Art drawing and learning: Meaning making as pedagogical approach in Master's graduate classes. Issue 3 (6th December 2012) - Chiang, Linda H.
This article argues that drawing may be used to retrieve prospective teachers' meta cognition and allow them to be constructive teachers. Participants in this enquiry are 57 teacher candidates from a Master of Arts in Teaching programme in Southern California. This pedagogical process required teacher candidates to apply cognitive concepts in creative and reflective drawings. Through these drawings the participants retrieved their previous experiences and knowledge by filling spaces to express their experience and thinking. Cognitive development U-shaped curve and Aesthetic development theories were applied to discuss participants' artistic development. This enquiry shows that pedagogical practice allows those teacher candidates to use cognitive theories in drawing. It also provides participants creative ways to understand themselves and their future students.